Agrarian transformation among tribals: from migrants to farmer irrigators - Mukherji, Aditi; Verma, S.; Rath, P. (International Water Management Institute, 2003)
Research highlight based on a paper titled Impact of participatory irrigation management on tribals in South Gujarat